The role of wages in the migration of health care professionals from developing countries - Adams Orvill; Diallo Khassoum; Zurn Pascal; Vujicic Marko; Dal Poz Mario R (BMC, 2004)
Abstract Several countries are increasingly relying on immigration as a means of coping with domestic shortages of health care professionals. This trend has led to concerns that in many of the source countries - especially within Africa - the outflow of health care professionals is adversely affecting the health care system. This paper examines the role of wages in the migration decision and discusses the likely effect of wage increases in source countries in slowing migration flows. This paper uses data on wage differentials in the health care sector between source country and receiving country (adjusted for purchasing power parity) to test the hypothesis that larger wage differentials lead to a larger supply of health care migrants. Differences in other important factors affecting migration are discussed and, where available, data are presented. There is little correlation between the supply of health care migrants and the size of the wage differential between source and destination country. In cases where data are available on other factors affecting migration, controlling for these factors does not affect the result. At current levels, wage differentials between source and destination country are so large that small increases in health care wages in source countries are unlikely to affect significantly the supply of health care migrants. The results suggest that non-wage instruments might be more effective in altering migration flows.